Retorika Perlawanan Ayatullah Khamenei dalam Konflik Iran–Israel 2025: Analisis Wacana Kritis - Najahan Musyafak (Communicatus: Jurnal Ilmu komunikasi, 2026)
This study analyzes twelve statements made by Ayatollah Sayyid Ali Khamenei during the 12-day conflict between Iran and Israel in June 2025 using Fairclough’s Critical Discourse Analysis (CDA) approach. The study aims to examine how Khamenei’s rhetoric functions as a political communication strategy that not only responds to external threats but also constructs ideological identity and political legitimacy for Iran. The analysis employs Burke’s seven-step rhetorical framework, including statement identification, symbolic language, grammatical structure, implicit ideology, political motivation, rhetorical context, and intertextuality. The findings reveal that Khamenei’s rhetoric frames Iran as a moral and political force resisting the dominance of the United States and Israel. Expressions such as “America has been slapped in the face” and “Israel is a dog controlled by the US” function as symbolic representations of resistance loaded with emotional and historical meaning. The study demonstrates that political language does not merely reflect geopolitical conflict but actively constructs collective identity and legitimacy through antagonistic narratives. This research contributes to the development of political communication and critical discourse studies in contemporary geopolitical contexts.